Review Potensi Siklon Tropis yang Menyebabkan Banjir Pantai - Ni Made Praptiwi Rahayu; Engki A. Kisnarti (Universitas Hang Tuah, 2023)
Tropical cyclones can also be said to be large storm systems that occur every year. The pressure difference that occurs from vortex circulation activity causes tropical cyclones to form in waters close to the equator. Tropical cyclones are one of the triggers for hydrometeorological disasters. The impact of tropical cyclones can be felt in Indonesia, both directly (flash floods) and indirectly (lower temperatures) when far from the source of tropical cyclones. To be able to determine the movement of tropical cyclone Paddy, this was done using the satellite image observation method, namely the Himawari-8 satellite. Tropical cyclones can also be measured by comparing several models, to predict tropical cyclones. This model helps to predict in order to minimize the impact of tropical cyclones which can cause coastal flooding. This data can be processed with a first order model because it is more stable. Therefore, satellite imagery can be used to see, understand and analyze the movement of tropical cyclones.